2014
DOI: 10.1242/jeb.105361
|View full text |Cite
|
Sign up to set email alerts
|

Titin force is enhanced in actively stretched skeletal muscle

Abstract: The sliding filament theory of muscle contraction is widely accepted as the means by which muscles generate force during activation. Within the constraints of this theory, isometric, steady-state force produced during muscle activation is proportional to the amount of filament overlap. Previous studies from our laboratory demonstrated enhanced titin-based force in myofibrils that were actively stretched to lengths which exceeded filament overlap. This observation cannot be explained by the sliding filament the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
139
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(145 citation statements)
references
References 59 publications
6
139
0
Order By: Relevance
“…These initial observations of 'passive force enhancement' demonstrated that, following active stretch, titin-based force remained greater after deactivation than its passive force at corresponding lengths in cat soleus muscle (Herzog and Leonard, 2002). Titin force enhancement was investigated in rabbit (and later, mouse) psoas myofibrils stretched actively beyond filament overlap (Leonard and Herzog, 2010;Powers et al, 2014). These studies showed a 400% increase in titin-based force in sarcomeres stretched actively to 6.0 μm, when compared with titinbased force in sarcomeres passively stretched to the same length, greatly exceeding the 20% increase in titin force previously measured following deactivation of actively stretched myofibrils (Joumaa et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…These initial observations of 'passive force enhancement' demonstrated that, following active stretch, titin-based force remained greater after deactivation than its passive force at corresponding lengths in cat soleus muscle (Herzog and Leonard, 2002). Titin force enhancement was investigated in rabbit (and later, mouse) psoas myofibrils stretched actively beyond filament overlap (Leonard and Herzog, 2010;Powers et al, 2014). These studies showed a 400% increase in titin-based force in sarcomeres stretched actively to 6.0 μm, when compared with titinbased force in sarcomeres passively stretched to the same length, greatly exceeding the 20% increase in titin force previously measured following deactivation of actively stretched myofibrils (Joumaa et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…Nevertheless, active sarcomeres are routinely stretched during movement and generate more force following stretch than can be explained by cross-bridges alone (Herzog and Leonard, 2002). Because this additional force depends on the magnitude but not the speed of stretch, and because it results in increased passive force ( passive residual force enhancement), it has been speculated that titin contributes to this unexplained extra force (Herzog and Leonard, 2002;Leonard and Herzog, 2010;Nishikawa et al, 2012;Powers et al, 2014Powers et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leonard and Herzog (2010) and Powers et al (2014) observed that titinbased muscle stiffness increases upon activation. It is plausible that the mechanism by which titin increases active muscle stiffness is affected by the mdm mutation (Nishikawa et al, 2012;Herzog, 2014).…”
Section: Mass and Stiffness Modelmentioning
confidence: 99%
“…However, Nishikawa et al (2012) and Herzog (2014) have suggested that titin's contribution to muscle stiffness may increase upon muscle activation by binding to the thin filament. Leonard and Herzog (2010) and Powers et al (2014) have shown that titin-based stiffness increases during muscle activation.…”
Section: Introductionmentioning
confidence: 99%